Seasonal Dynamics, Record of Ticks Infesting Humans, Wild and Domestic Animals and Molecular Phylogeny of Rhipicephalus microplus in Khyber Pakhtunkhwa Pakistan - Ali, Abid; Khan, Munsif Ali; Zahid, Hafsa; Yaseen, Pir Muhammad; Qayash Khan, Muhammad; Nawab, Javed; Ur Rehman, Zia; Ateeq, Muhammad; Khan, Sardar; Ibrahim, Mohammad (Frontiers in Physiology, 2019)
Although ticks prevalent in various agro-systems of Pakistan are associated with economic losses, information is still missing about the tick’s diversity, hosts they infest, seasonal dynamics and molecular phylogeny of Rhipicephalus microplus in Khyber Pakhtunkhwa (KP) Pakistan. This study for the first time enlisted ticks infesting diverse hosts including humans in various regions of KP. A total of 8,641 ticks were collected across the northern, southern and central regions of KP and were morpho-taxonomically categorized into six genera comprising 17 species, R. microplus (n = 3,584, 42%), Hyalomma anatolicum (n = 2,253, 27%), Argas persicus (n = 1,342, 16%), Hya. impeltatum (n = 586, 7%), R. turanicus (n = 161, 2%), R. haemaphysaloides (n = 142, 2%), R. annulatus (n = 132, 2%), Hae. montgomeryi (n = 123, 1.4%), Hya. marginatum (n = 110, 1.3%), R. sanguineus (n = 34, 0.4%), and Hae. longicornis (n = 31, 0.4%). Ticks infesting wild animals included Amblyomma gervaisi, Amb. exornatum, Amb. latum, Dermacentor marginatus, and Hae. indica, while ticks collected from humans included R. microplus, R. annulatus, Hya. anatolicum, Hya. marginatum, and Hae. punctata. The overall prevalence of ticks infesting domestic animals was 69.4% (536/772). Among animal hosts, cattle were found highly infested (87.2%, 157/180) followed by buffalos (79%, 91/114), domestic fowls (74.7%, 112/150), goats (68.3%, 82/120), dogs (66.7%, 32/48), horses (61.3%, 49/80), and sheep (16.3%, 13/80). Analysis revealed that the tick burden significantly differed among domestic animals and was found to be high in cattle, followed by buffalos, goats, sheep, domestic fowl, dogs, and horses. Seasonal patterns of ticks distribution showed highest prevalance in July, August, and September due to the prevailing high temperature and humidity during these months. The phylogenetic analysis of cattle tick R. microplus based on partial mitochondrial cytochrome oxidase subunit I (COX1), 16S ribosomal RNA (16S rRNA) and internal transcribed spacer 2 (ITS2) sequences, revealed that R. microplus prevalent in this region belongs to clade C which include ticks originating from Bangladesh, Malaysia, and India. Further large scale studies across the country are necessary to explore the molecular and cross breeding aspects at the geographical overlapping of various tick species and their associated pathogens to facilitate designing control strategies as well as awareness against tick infestation in the region.